Potensi Trichoderma sp. Asal Tanah Gambut Sebagai Agensia Pengendali Biologi Jamur Patogen Terbawa Benih Padi - Maulina Aizah, Shinta; Purnawati, Arika; Prasetyawati, Endang Triwahyu (BIOEDUSCIENCE, 2024)
Background: Rice (Oryza sativa) is the world's second most important food crop after wheat. In Indonesia, more than 90% of the population consumes rice, and there is a very high level of dependence, so rice has essential value for the Indonesian population. However, this has not been accompanied by the availability of healthy seeds because many pathogenic fungi are carried by rice seeds, such as Rhizopus sp., Mucor sp., Aspergillus sp., Fusarium sp., Curvularia sp. Seed treatment using synthetic fungicides is an effort to control pathogenic fungi on seeds, but it hurts seeds, humans, and the environment. A safe control alternative is using biological agents, namely the fungus Trichoderma sp. isolated from peatlands and has an antibiosis mechanism. The research aimed to test the potential of the fungus Trichoderma sp. from peat soil as a biological control agent for pathogenic fungi carried by rice seeds (Oryza sativa). Methods: The test uses the incubation method on PDA media and the growing test method on sterile soil media. The research used a completely randomized design with a factor of 2 isolates of Trichoderma sp. and eight replications and data analysis using BNJ5%. Results: isolation results obtained two isolates of Trichoderma sp. (P1 and P2), two isolates of Trichoderma sp. (P1 and P2) were able to suppress the level of pathogenic fungal infections carried by rice seeds in the incubation method using PDA media and the growing on test method, 3.75%, two isolates of Trichoderma sp. able to increase the germination capacity of rice seeds by P1 (12.50%) and P2 (31.25%) respectively. Conclusions: Two isolates of Trichoderma sp. (P1 and P2) could suppress the level of pathogenic fungal infections carried by rice seeds in the incubation method using PDA media and in the growing on test method. Apart from that, two isolates of Trichoderma sp.